2 Answers | Add Yours
We have to determine the result of the sum of 2 ratios.
To calculate the sum of 2 ratios that do not have a common denominator we'll have to calculate the LCD(least common denominator) of the 2 ratios.
We notice that LCD = (1+i)(1-i)
We notice also that the product (1+i)(1-i) is like:
(a-b)(a+b) = a^2 - b^2
We'll write instead of product the difference of squares, where a = 1 and b = i.
LCD = (1+i)(1-i)
LCD = 1^2 - i^2
We'll write instead of i^2 = -1
LCD = 1 - (-1)
LCD = 2
Now, we'll multiply the first ratio by (1-i) and the second ratio by (1+i):
i(1-i)/2 + i(1+i)/ 2
We'll remove the brackets:
(i - i^2 + i + i^2)/2
We'll eliminate like terms:
We'll simplify and we'll get:
z1 + z2 = i(1-i)/2 + i(1+i)/ 2
i(1-i)/2 + i(1+i)/ 2 = i
The result is a complex number, whose real part is 0 and imaginary part is 1
We’ve answered 317,396 questions. We can answer yours, too.Ask a question